Determinants affecting the high employee turnover in Saint-Gobain Malaysia Sdn. Bhd / Tuan Munirah Tuan Zahari - Tuan Zahari, Tuan Munirah (Faculty of Business and Management, 2017)
The purpose of this study is to analyze determinants affecting the high employee turnover in Saint-Gobain Malaysia Sdn. Bhd. Turnover is a worker intended to leave from the company that is he or she is working currently. A total number of 118 questionnaires were distributed to the employees and only 96 were return fully answered. The research is based on a sample size of 92 respondents who are working in Saint-Gobain Malaysia Sdn. Bhd. Each variables’ effect which are employee turnover, work overload, compensation and benefits and work repetitiveness will be assessed in empirical analysis of data using SPSS Statistic 20 software. Result reveal that employee turnover is positively related with work overload, compensation and benefits and work repetitiveness. The overall, these findings and recommendations can be used by the organization, Saint-Gobain Malaysia Sdn. Bhd to improve in the future and lessen the turnover issues.